SUFFA RADIO OBSERVATORY IN UZBEKISTAN: RADIOMETRIC RESEARCH IN THE RADIO RANGE - Raupov, Dilshod; Hotamov, Jahongir (Физико-технологического образование, 2021)
Radio Astronomical Observatory of Suffa, and new proposals for radioastroclimatic (seeing) studies for atmospheric radio prediction are described